Developmental environment mediates male seminal protein investment in Drosophila melanogaster. (20th August 2015) - Wigby, Stuart; Perry, Jennifer C.; Kim, Yon‐Hee; Sirot, Laura K.
Summary: Males of many species fine‐tune their ejaculates in response to sperm competition risk. Resource availability and the number of competitors during development can also strongly influence sperm production. However, despite the key role of seminal proteins in mediating reproductive processes, it is unclear whether seminal protein investment is dependent on the developmental environment. We manipulated the developmental environment of Drosophila melanogaster by rearing flies at low and high density. As expected, this resulted in large and small (i.e. high and low condition) adult phenotypes, respectively. As predicted, large males produced more of two key seminal proteins, sex peptide (SP) and ovulin, and were more successful at obtaining matings with both virgin and previously mated females. However, there was only a weak and non‐significant trend for large males to transfer more absolute quantities of SP at mating, and thus, small males ejaculated proportionally more of their stored accessory gland SP resources. Males transferred more receptivity‐inhibiting SP to large females. Despite this, large females remated more quickly than small females and thus responded to their developmental environment over and above the quantity of SP they received. The results are consistent with two non‐mutually exclusive hypotheses. First, flies might respond to condition‐dependent reproductive opportunities, with (i) small males investing heavily in ejaculates when mating opportunities arise and large males strategically partitioning SP resources and (ii) small females remating at reduced rates because they have higher mating costs or need to replenish sperm less often. Second, flies may be primed by their larval environment to deal with similar adult population densities, with (i) males perceiving high density as signalling increased competition, leading small males to invest proportionally more SP resources at mating and (ii) females perceiving high density as signalling abundant potential mates, leading to a higher sexual receptivity threshold. Thus, by influencing the mating frequencies of both sexes, as well as the quantity of seminal proteins produced by males and received by females, the developmental environment is likely to have far‐reaching and sex‐specific consequences for sexual selection and sexual conflict. Abstract : Lay Summary